Sterols accelerate degradation of hamster 3-hydroxy-3-methylglutaryl coenzyme A reductase encoded by a constitutively expressed cDNA. - Chin, D J (1985)
A recombinant plasmid containing a full-length cDNA for hamster 3-hydroxy-3-methylglutaryl coenzyme A reductase was introduced by calcium phosphate-mediated transfection into UT-2 cells, a mutant line of Chinese hamster ovary cells that lack 3-hydroxy-3-methylglutaryl coenzyme A reductase activity and thus require low density lipoprotein-cholesterol and mevalonate for growth. We selected a line of permanently transfected cells, designated TR-36 cells, that expressed high levels of 3-hydroxy-3-methylglutaryl coenzyme A reductase activity and thus grew in the absence of low density lipoprotein and mevalonate. Constitutive synthesis of reductase mRNA in TR-36 cells was driven by the simian virus 40 early promoter, and therefore the mRNA was not suppressed by sterols, such as 25-hydroxycholesterol or cholesterol derived from low density lipoprotein, which normally suppresses transcription of reductase mRNA when the reductase gene is driven by its own promoter. Although TR-36 cells continued to synthesize large amounts of reductase mRNA and protein in the presence of sterols, reductase activity declined by 50 to 60%. This decline was caused by a twofold increase in the rate of degradation of preformed enzyme molecules. The current data demonstrate that sterols accelerate the degradation of reductase protein independently of any inhibitory effect on the synthesis of the protein.